PRIMATA / ilustrasi, David Daniel Pahala ; editor, Broto Raharjo, Danu Nugraha, Margaretha H. Eddy - Pahala, David Daniel; Raharjo, Broto; Nugraha, Danu; Eddy, Margaretha (Erlangga)
[28] hlm ilus 22 cm